Assessing Water Rights in China - Wang, Yahua (Water Resources Development and Management,, 2018)
This book presents a model for describing the hierarchical concept of China's water rights structure, one which takes into account pioneering theories on natural resources and environmental institutional economics. It highlights the basic theory of water rights, with a view to helping Chinese policymakers acquire a deeper understanding of water rights and the need for a reform program in the long-term development of water-poor China. To do so, it draws on three main sources: Cheung SNS's "Economic Explanation", Douglas C. North's "New Economic History" and Ray Huang's "Macro History". The book makes two essential contributions: it elaborates the hierarchical water governance structure in China, which originated in the Qin Dynasty that unified the country 2000 years ago and has been employed without interruption ever since; further, it constructs a choice model for water governance structures and advances the logic of making structural choices with minimum transaction costs under constraint conditions, while also explaining the inherent nature of China's choice for the hierarchical structure from the perspectives of management cost and cooperation cost. As such, the book enriches and builds on the theories of the "water governance" school represented by Karl Marx, Karl Wittfogel and Ray Huang, laying the foundation for the further study of water rights theory in contemporary China.